On Polymer Expansion for Gibbsian States of Nonequilibrium Systems of Interacting Brownian Oscillators - Skrypnik, W.I. (Український математичний журнал, 2003)
The convergence of polymer cluster expansions for correlation functions of general Gibbs oscillator-type systems and related nonequilibrium systems of Brownian oscillators is established. The initial states for the latter are Gibbsian. It is proved that the sequence of the constructed correlation functions of the nonequilibrium system is a generalized solution of a diffusion BBGKY-type hierarchy. Встановлено збіжність кластерних розкладів для кореляційних функцій загальних граткових гіббсівських систем осциляторного типу та споріднених нерівноважних систем броунівських осциляторів у термодинамічній границі. Початкові стани для останніх є гіббсівськими. Доведено, що послідовність побудованих функцій нерівноважної системи є узагальненим розв'язком дифузійної ієрархії типу ББГКІ.